Multisensory processing in review: From physiology to behaviour - NEWELL, FIONA (Brill Academic, 2010)
Research in multisensory processes has exploded over the last decade. Tremendous advances have been made in a variety of fields from single-unit neural recordings and functional brain imaging through to behaviour, perception and cognition. These diverse approaches have highlighted how the senses work together to produce a coherent multimodal representation of the external world that enables us to function better by exploiting the redundancies and complementarities provided by multiple sensory modalities. With large numbers of new students and researchers being attracted to multisensory research, and the multi-disciplinary nature of the work, our aim in this review is to provide an overview of multisensory processing that includes all fields in a single review. Our intention is to provide a comprehensive source for those interested in learning about multisensory processes, covering a variety of sensory combinations and methodologies, and tracing the path from single-unit neurophysiology through to perception and cognitive functions such as attention and speech.
PUBLISHED
Keywords: multisensory; perception; neuroimaging; behaviour; neurophysiology